2018
DOI: 10.1111/1440-1681.12899
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles and challenges for tissue engineering and regenerative medicine: Australian nuances

Abstract: The clinical need and historical approaches to tissue engineering as applied to regenerative medicine are introduced, along with comments on activities in this field around Australia, and then the huge advances for tissue culture studies are discussed (Part A). Combinations of human stem cells and new approaches for generating bioscaffolds present great opportunities for in vitro studies of basic biology and physiology, drug testing and high throughput screening for the pharmaceutical industry, and the advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 103 publications
0
29
0
Order By: Relevance
“…Revascularization of implanted tissue engineered scaffolds at the human scale is one of the major challenges. [148] Another major challenge is the cell seeding on surface and within the scaffold. Some findings showed that seeding of autologous bone marrow-derived mesenchymal stem cells (MSCs) on PGA scaffold coated with poly 4-hydroxybutyrate (P4HB) gave a promising autologous trileaflet heart valve.…”
Section: Potential Future Work and Their Associated Challengesmentioning
confidence: 99%
“…Revascularization of implanted tissue engineered scaffolds at the human scale is one of the major challenges. [148] Another major challenge is the cell seeding on surface and within the scaffold. Some findings showed that seeding of autologous bone marrow-derived mesenchymal stem cells (MSCs) on PGA scaffold coated with poly 4-hydroxybutyrate (P4HB) gave a promising autologous trileaflet heart valve.…”
Section: Potential Future Work and Their Associated Challengesmentioning
confidence: 99%
“…The ECM and cellular composition of different tissues vary widely between cell types and they each pose their own engineering challenges [ 49 , 54 ]. It is vital for biomaterials to not only mimic the structural components of the ECM, but to also have the ability to promote adhesion, differentiation and proliferation of cells [ 49 , 55 , 56 ]. Over the last three decades, there has been an increase in publications developing various types of biomaterials as shown in the key term maps for topic set 2.…”
Section: Discussionmentioning
confidence: 99%
“…These major problems need to be realistically addressed when proposing stem cell therapies for muscular dystrophies. Another therapeutic strategy for delivering myogenic stem cells, is the exciting field of tissue engineering that aims to build new muscle constructs to replace muscles that are unable to regenerate due to some impaired intrinsic capacity of muscle stem cells; while this holds great promise for many creative tissue culture studies of muscle cells, there remain serious challenges for clinical applications [8] .…”
Section: Duchenne Muscular Dystrophy: Groundsmentioning
confidence: 99%